Probiotic Supplementation for Rheumatoid Arthritis: A Promising Adjuvant Therapy in the Gut Microbiome Era - Ferro, Margarida; Charneca, Sofia; Dourado, Eduardo; Guerreiro, Catarina Sousa; Fonseca, João Eurico (Frontiers in Pharmacology, 2021)
Rheumatoid arthritis (RA) is a chronic immune-mediated inflammatory disease that ultimately leads to joint destruction and functional disability. Although the exact aetiology of RA is not fully understood, it is well established that gut microbiota (GM) plays a vital role in the pathogenesis of RA, with accumulating evidence suggesting that gut dysbiosis induces a chronic inflammatory response that may be linked to disease development. Of interest, patients with RA have significant changes in the intestinal microbiota compared to healthy controls, and several studies have suggested the use of probiotics as a possible adjuvant therapy for RA. Benefits of probiotic supplementation were reported in animal models of arthritis and human studies, but the current evidence regarding the effect of probiotic supplementation in the management of RA remains insufficient to make definite recommendations. Several different strains of Lactobacillus and Bifidobacteria, as single species or in mixed culture, have been investigated, and some have demonstrated beneficial effects on disease activity in RA human subjects. As of now, L. Casei probiotic bacteria seems to be the strongest candidate for application as adjuvant therapy for RA patients. In this review, we highlight the role of GM in the development and progression of RA and summarize the current knowledge on the use of probiotics as a potential adjuvant therapy for RA. We also review the proposed mechanisms whereby probiotics regulate inflammation. Finally, the role of fermented foods is discussed as a possible alternative to probiotic supplements since they have also been reported to have health benefits.